Central diabetes insipidus in neonate born at 24 weeks of pregnancy – Case report and review of literature - Szpecht, Dawid; Nowak, Irmina; Ciesielska, Agnieszka; Szymankiewicz, Marta; Gadzinowski, Janusz (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Background: Central diabetes insipidus is a condition associated with the dysfunction of hypothalamic-pituitary axis and, consequently impaired synthesis and secretion of vasopressin. This condition is rarely found in preterm neonates which is why we decided to report it. Also, there are no guidelines on how to treat this condition in neonates, so it is important to share our experience and provide information on the therapies we used therapies and their results. Case presentation: In our paper we describe a case of a male infant born at 24 weeks of gestation, who suffered an intraventricular hemorrhage of grade IV severity. The hemorrhage caused damage to the posterior pituitary lobe which in turn resulted in central diabetes insipidus. Oral desmopressin therapy was administered. Conclusion: In our case we achieved positive clinical results – normalization of diuresis and natremia. It shows that oral desmopressin can be taken into consideration for treatment of diabetes insipidus in preterm neonates. This case report can be useful for both neonatologists and endocrinologists. It is also important to compare our case with similar cases to expand our knowledge about this rare disease in neonates and to find possible therapies.